Hereditary ataxias and paraparesias: clinical and genetic update. Issue 4 (August 2018) - Parodi, Livia; Coarelli, Giulia; Stevanin, Giovanni; Brice, Alexis; Durr, Alexandra
Abstract : Purpose of review: This review aims at updating the clinical and genetic aspects of hereditary spastic paraplegias (HSPs) and hereditary cerebellar ataxias (HCAs), focusing on the concept of spastic-ataxia phenotypic spectrum and on newly identified clinical overlaps with other neurological and nonneurological diseases. Recent findings: Next-generation sequencing (NGS) has allowed the discovery of new genes involved in HSPs and HCAs. They include new HCAs genes such as GRM1 (SCA44), FAT2 (SCA45), PLD3 (SCA46), SCYL1 (SCAR21), UBA5 (SCAR24) and XRCC1 (SCAR26) as well as CAPN1 (SPG76) and CPT1C (SPG73) in HSPs. Furthermore, NGS allowed enriching known genes phenotype, reinforcing the overlap between HSPs and HCAs defining the spastic ataxia spectrum. Clear examples are the expanded phenotypes associated with mutations in SPG7, PNPLA6, GBA2, KIF1C, CYP7B1, FA2H, ATP13A2 and many others. Moreover, other genes not previously linked to HCAs and HSPs have been implicated in spastic or ataxic phenotypes. Summary: The increase of HSPs and HCAs-related phenotypes and the continuous discovery of genes complicate clinical diagnostic in practice but, at the same time, it helps highlighting common pathological pathways, therefore opening new ways to the development of common therapeutic approaches.